From Digital Mental Health to Digital Social and Emotional Wellbeing: How Indigenous Community-Based Participatory Research Influenced the Australian Government’s Digital Mental Health Agenda - James Bennett-Levy; Judy Singer; Darlene Rotumah; Sarah Bernays; David Edwards (International Journal of Environmental Research and Public Health, 2021)
This paper describes the first six years of a government-initiated project to train Indigenous health professionals in digital mental health (d-MH). It illustrates how community-based participatory research (CBPR) methods were used to enable this “top-down” project to be transformed into a ‘ground-up’ community-guided process; and how, in turn, the guidance from the local Indigenous community partners went on to influence the national government’s d-MH agenda. The CBPR partnership between five community partners and a university rural health department is described, with illustrations of how CBPR harnessed the community’s voice in making the project relevant to their wellbeing needs. The local Indigenous community’s involvement led to a number of unexpected outcomes, which impacted locally and nationally. At an early stage, the conceptual framework of the project was changed from d-MH to the culturally-relevant Indigenous framework of digital social and emotional wellbeing (d-SEWB). This led to a significant expansion of the range and type of digital resources; and to other notable outcomes such as successful advocacy for an Aboriginal-specific online therapy program and for a dedicated “one-stop-shop” d-SEWB website, Wellmob, which was funded by the Australian government in 2019–2021. Some of the implications of this project for future Indigenous CBPR projects are discussed.